35 W continuous-wave Ho:YAG single-crystal fiber laser. (2020) - Zhao, Yongguang; Wang, Li; Chen, Weidong; Wang, Jianlei; Song, Qingsong; Xu, Xiaodong; Liu, Ying; Shen, Deyuan; Xu, Jun; Mateos, Xavier; Loiko, Pavel; Wang, Zhengping; et al.
Abstract : We report on a high-power Ho:YAG single-crystal fiber (SCF) laser inband pumped by a high-brightness Tm-fiber laser at 1908 nm. The Ho:YAG SCF grown by the micro-pulling-down technique exhibits a propagation loss of 0.05± 0.005 cm^-1 at 2.09 [STIX]x03BCm . A continuous-wave output power of 35.2 W is achieved with a slope efficiency of 42.7%, which is to the best of our knowledge the highest power ever reported from an SCF-based laser in the 2 [STIX]x03BCm spectral range.